Developing English Speaking Skill for Students at LPK Cahaya Khansaa Cimahi - Heryono, Heri; Zuraida, Ida; Hendar,; Lukitawati, Meita (International Journal of Psychosocial Rehabilitation, 2020)
Community service is one of the responsibilities for lecturers to contribute to the people around. Community Service Program is technically as an activity in an effort to carry out one of the dharma (obligations) of Higher Education. Therefore, research and community service are which the elements of the Higher Education Tri Dharma that should be carried out by all lecturers, including English lecturers especially at Widyatama University Bandung. The English Study Program at Widyatama University in Bandung roles as an institution whose main activity is developing English language skills; thus it leads to provide debriefing and practice in the field of language related to the world of work for students at LPK Cahaya Khansaa Cimahi through Community Service activities. The form of English training was focused on developing speaking proficiency. The method used in the program was interview method by applying job interview practice, since the common purpose of the participants studying at LPK was for getting job. The output of the program was score improvement resulted by the participants. From the results of the training, it obtained very significant results that could be observed from the participants. After conducting the pre-test section, the program was continued with the provision of material in the form of conversations, introduction of self and others and job interview practice and simulation sessions. The results were obtained in the form of a final score with a mean value of 19.35 after previously 18.70 at the time of the pre-test. This proved that the interview method and the provision of materials assisted participants in improving (scores) English speaking skill, especially at LPK Cahaya Khansaa.